Graphene Oxide: Synthesis, Characterization, And Applications In Energy Storage (Journal of Pharmaceutical Negative Results, 2022)
A single sheet of graphene oxide known as graphene oxide (GO) has demonstrated great promise for energy conversion and storage applications. It has drawn interest due to its unique structure and improved qualities, which make it appropriate for application in a range of energy conversion and storage systems. The potential applications of GO and its composites in water electrolyzers, fuel cells, batteries, and supercapacitors have been investigated. According to recent studies, GO has the ability to completely transform the supercapacitor technology by providing better energy storage capacities, increased performance, and affordable solutions. Because of its two-dimensional structure, exceptional electrical conductivity, large surface area, and superior mechanical strength, graphene oxide (GO) is a great option for applications that need high power output or short bursts of energy. Moreover, high-capacity energy storage in lithium-ion batteries and supercapacitors has been achieved through the use of reduced graphene oxide (rGO) nanocomposites, underscoring the potential of graphene-based materials in energy storage applications. GO's cost-effectiveness and wide availability make it a good substitute for pricey materials, which increases its appeal for energy storage applications. Better capacitance and charge-discharge rates result from the precise controllable characteristics of graphene oxide on the electrode's surface. To sum up, GO has great potential to advance energy storage technologies by providing improved performance and affordable options.